The seroprevalence of Coxiella burnetii in Erzincan, Turkey: Identification of the risk factors and their relationship with geographical features - Cikman, Aytekin; Aydin, Merve; Gulhan, Baris; KARAKEÇİLİ, FARUK; ÖZÇİÇEK, ADALET; Kesik, Ozan Arif; Parlak, Mehmet; OZCELIK, Fatih; Gultepe, BİLGE; SÜMBÜL, BİLGE (My University, 2017)
Background & objectives: Coxiella burnetii (C. burnetii) bacterium, the causative agent of Q fever has regained importance due to the increasing cases of infections and outbreaks. A cross-sectional descriptive study was conducted to investigate the seroprevalence of C. burnetii in human populations of Erzincan province located in the eastern Turkey, identify the risk factors, and to explore the relationship between geographical features.